2021
DOI: 10.1017/s0954422421000147
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic aspects of carotenoid health benefits – where are we now?

Abstract: Dietary intake and tissue levels of carotenoids have been associated with a reduced risk of several chronic diseases, including cardiovascular diseases, type 2 diabetes, obesity, brain related diseases and some types of cancer. However, intervention trials with isolated carotenoid supplements have mostly failed to confirm the postulated health benefits. It has thereby been speculated that dosing, matrix and synergistic effects, as well as underlying health and the individual nutritional status plus genetic bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 381 publications
(482 reference statements)
2
65
1
Order By: Relevance
“…In particular, correlations with α and ß-carotene were found [ 54 ]. The effects of carotenoid supplementation on gut composition are few, and a recent review tried to summarize the main findings by concluding that the “carotenoids–gut” interaction still represents a fundamental research question that must be addressed [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, correlations with α and ß-carotene were found [ 54 ]. The effects of carotenoid supplementation on gut composition are few, and a recent review tried to summarize the main findings by concluding that the “carotenoids–gut” interaction still represents a fundamental research question that must be addressed [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Carotenoids are a family of long conjugated isoprenoid pigments that have a cosmopolitan presence among the vegetal kingdom, as well as in photosynthetic organisms and fungi [146], whereas the animal kingdom lacks the ability to produce them, probably due to the evolutionary loss of the required genes needed to encode the enzymes for carotenoid biosynthesis [147]. These accessory pigments are part of a light-harvesting antenna complex in the thylakoid membrane of chloroplasts [146], and contribute to the photosynthetic process by enhancing light harvest in the blue spectrum, and thus extending the light-absorption range [147]. Additionally, they have a key role as photo-protective and antioxidant agents, by shielding organisms from excess light energy, by performing the thermal dissipation of any energy surplus in the photosynthetic apparatus, and by acting as direct quenchers of reactive oxygen damage [148][149][150].…”
Section: Distribution Properties and Structurementioning
confidence: 99%
“…Recent reviews regarding carotenoids (from 2016 onwards) can be found, that deal with their potential health benefits [147,151,[162][163][164], bio-accessibility [148,164], metabolism and biosynthesis [149,165], dietary sources [158], production [157,[166][167][168], extraction and analysis [158], and biotechnological potential [167]; again, most of these examples focus on either microalgae or fungi or, at least, they are not solely focused on macroalgae. By searching the word "carotenoid", Patentscope holds 4701 registered patents, using the search field "front page" [16].…”
Section: Biotechnological Potential and Applicationsmentioning
confidence: 99%
“…Although dietary intake and tissue levels of provitamin A and related carotenoids have been associated with reduced risk of several types of cancer and many of the same carotenoids have shown anticancer activity in preclinical models, both in vitro and in vivo, intervention trials with isolated carotenoid supplements other than lycopene have not shown anticancer activity, and in fact 1% of current and former smokers as well as patients with a history of asbestos exposure who took long-term high daily doses of isolated carotenoid supplements actually developed lung cancer which similar patients in the control group did not [21].…”
Section: Hallmark #1: Genomic Instabilitymentioning
confidence: 99%